Microsoft Office 2016 step by step - Lambert, Joan; Frye, Curtis, 1968- (Step by step (Redmond, Wash.), 2015)
This is learning made easy. Get productive fast with Office 2016 and jump in wherever you need answers--brisk lessons and colorful screen shots show you exactly what to do, step by step.